2019
DOI: 10.1002/mnfr.201801148
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 Polyunsaturated Fatty Acids Inhibit IL‐17A Secretion through Decreased ICAM‐1 Expression in T Cells Co‐Cultured with Adipose‐Derived Stem Cells Harvested from Adipose Tissues of Obese Subjects

Abstract: Scope: Obese adipose tissue (AT) is infiltrated by inflammatory immune cells including IL-17A-producing-T (Th17) cells.It has been previously demonstrated that adipose-derived stem cells from obese (ob-ASCs), but not lean AT promote Th17 cells. Because n-3 PUFAs are known to inhibit obese AT inflammation, it is tested here whether they could inhibit ob-ASC-mediated IL-17A secretion. Methods and Results: The n-3 PUFA precursor, alpha-linolenic acid (ALA), or its derivatives, eicosapentaenoic, or docosahexaenoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
(115 reference statements)
1
12
0
Order By: Relevance
“…Whereas markers of platelet aggregation and activation increased in activated ASC/MNC co-cultures, no difference was observed whether G-HSA or HSA was present. ICAM-1 expression, which has also been shown to increase in endothelial cells under the influence of RAGE activation[ 30 ] and in co-cultures of obese ASC with T cells[ 31 ], did not increase in the presence of G-HSA.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas markers of platelet aggregation and activation increased in activated ASC/MNC co-cultures, no difference was observed whether G-HSA or HSA was present. ICAM-1 expression, which has also been shown to increase in endothelial cells under the influence of RAGE activation[ 30 ] and in co-cultures of obese ASC with T cells[ 31 ], did not increase in the presence of G-HSA.…”
Section: Resultsmentioning
confidence: 99%
“…There were no analyses of cell function, such as cytokine secretion, because these measurements were not required to address the primary aim of the study. Nevertheless, previous studies have shown that omega-3 PUFA-induced changes in cytokine mRNA levels, including IL-17A and IL-5 in human [ 55 ] and murine [ 56 ] T cells or PBMCs, are related directly to their concentration in cell culture supernatants. Therefore, although the present study did not investigate whether changes in cytokine mRNA levels were associated with differences in their respective concentrations, it is probable that differences in gene expression would have altered cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported decreased expression of genes encoding proteins involved in pro-inflammatory pathways in human, animal and cellular models in response to EPA and/or DHA. For example, a recent study revealed beneficial effects of n-3 PUFA in IL-17A-related inflammatory pathologies through down-regulation of intercellular adhesion molecule-1 expression in monocytes and adipose-derived stem cells (36) . In contrast, adipocyte-derived PGE 2 , a derivative of ARA, mediates recruitment of adipose tissue macrophages contributing to inflammation (37) .…”
Section: Discussionmentioning
confidence: 99%